2005
DOI: 10.1210/jc.2004-2363
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hyperandrogenemic and Metabolic Phenotype with Carotid Intima-Media Thickness in Young Women with Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS), a common endocrinopathy of women of reproductive age, is associated with the early appearance of multiple risk factors for cardiovascular disease, such as abdominal obesity, dyslipidemia, and diabetes mellitus. However, premature atherosclerosis of the carotid artery has not yet been demonstrated in young women with PCOS. Measurement of carotid intima-media thickness (IMT) is considered an easy and reliable index of subclinical atherosclerosis, which is predictive of subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
3
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 65 publications
5
97
3
14
Order By: Relevance
“…This suggested that Cholesterol particularly LDL-C fraction increase was responsible for atherosclerosis and increased mean carotid IMT among PCOS women. Our study has been supported by the findings of Vryonidou et al (21), who found significantly higher carotid IMT (0.58 vs 0.47 mm, P < 0.001) among young women with PCOS (17-35 yrs) as compared to healthy controls.…”
Section: Among Clinically Diagnosed Pcossupporting
confidence: 92%
“…This suggested that Cholesterol particularly LDL-C fraction increase was responsible for atherosclerosis and increased mean carotid IMT among PCOS women. Our study has been supported by the findings of Vryonidou et al (21), who found significantly higher carotid IMT (0.58 vs 0.47 mm, P < 0.001) among young women with PCOS (17-35 yrs) as compared to healthy controls.…”
Section: Among Clinically Diagnosed Pcossupporting
confidence: 92%
“…Conflicting results have been provided regarding the factors associated with impaired vascular reactivity in PCOS. The relationship with hyperandrogenemia is especially controversial, since the effect of the androgens was described as either adverse [10,25], neutral [24,26], or even protective in patients with PCOS [27]. However, the reports are more constant with regard to ET-1 and the deleterious effect that markers of hyperandrogenemia have on it [3,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…A control group composed of 32 women (age: 23.06 ±5.37 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), BMI: 25.87± 6.89 (16.88-42.86) kg/m 2 ) was selected as to be similar to the group of patients in terms of age and BMI. In the end though, our intention was not fully accomplished because there was still a significant difference in BMI between the groups.…”
Section: Study Protocolmentioning
confidence: 99%
“…However, the report by Orio et al ., showed a strong association between CIMT and the free androgen index that suggests a contribution of hyperandrogenemia to evolvement of atherosclerosis in PCOS . Contrarily, in a larger study raised CIMT was conversely correlated with plasma DHEAS and androstenedione concentrations, proposing a fascinating vasculoprotective influence of hyperandrogenemia in PCOS (Vryonidou, Papatheodorou et al 2005). Meyer et al also found a similar vasculoprotective effect of DHEAS in a study involving 80 obese women with PCOS, where higher DHEAS corresponded to notably lower CIMT (Meyer, McGrath et al 2005).…”
Section: Carotid Intima Media Thicknessmentioning
confidence: 90%